Blood pressure and all-cause mortality: a prospective study of nursing home residents. (2nd November 2016) - Rådholm, Karin; Festin, Karin; Falk, Magnus; Midlöv, Patrik; Mölstad, Sigvard; Östgren, Carl Johan
Abstract : Aim: to explore the natural course of blood pressure development and its relation to mortality in a nursing home cohort. Methods: a cohort of 406 nursing home residents in south east Sweden was followed prospectively for 30 months. Participants were divided into four groups based on systolic blood pressure (SBP) at baseline. Data were analysed using a Cox regression model with all-cause mortality as the outcome measurement; paired Student t -tests were used to evaluate blood pressure development over time. Results: during follow-up, 174 (43%) people died. Participants with SBP < 120 mmHg had a hazard ratio for mortality of 1.56 (95% confidence interval, 1.08–2.27) compared with those with SBP 120–139 mmHg, adjusted for age and sex. Risk of malnutrition or present malnutrition was most common in participants with SBP < 120 mmHg; risk of malnutrition or present malnutrition estimated using the Mini Nutritional Assessment was found in 78 (71%). The levels of SBP decreased over time independent of changes in anti-hypertensive medication. Conclusions: in this cohort of nursing home residents, low SBP was associated with increased all-cause mortality. SBP decreased over time; this was not associated with altered anti-hypertensive treatment. The clinical implication from this study is that there is a need for systematic drug reviews in elderly persons in nursing homes, paying special attention to those with low SBP.